Situational analysis an effective leadership style to improve the Indonesian tax service offices performance in the era of change - Reza Saleh; Mohammad Syamsul Maarif; Lukman M Baga; Herien Puspitawati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
This study aims to analyze the effectiveness of Tax Service Offices’ leaders in the era of economic turbulence. Tax Service Office provides counseling, services, and supervision to Taxpayers. As public organizations, Tax Service Offices can become more competitive by cultivating effective leaders who combine style-oriented strategies with capabilities reflected in leadership behavior. This study applied descriptive analysis conducted to several Tax Service Offices in Jakarta within the Directorate General of Taxes, with a total of 542 questionnaires distributed to their employees. The findings show that a combination of leadership styles, such as transformational, transactional, adaptive, responsive, innovative, and competent, is extremely needed in this era of change. In addition, the level of experience and education is one of the criteria to improve effective leadership in the Indonesian Tax Service Offices.